Scientific and Regulatory Policy Committee Review: Review of the Organisation for Economic Co-operation and Development (OECD) Guidance on the GLP Requirements for Peer Review of Histopathology. (October 2015) - Fikes, James D.; Patrick, Daniel J.; Francke, Sabine; Frazier, Kendall S.; Reindel, James F.; Romeike, Annette; Spaet, Robert H.; Tomlinson, Lindsay; Schafer, Kenneth A.
In 2014, the Organisation for Economic Co-operation and Development (OECD) issued guidance no. 16, Guidance on the GLP Requirements for Peer Review of Histopathology. The stated purpose of the guidance document is "to provide guidance to pathologists, test facility management, study directors and quality assurance personnel on how the peer review of histopathology should be planned, managed, documented, and reported in order to meet Good Laboratory Practice (GLP) expectations and requirements." On behalf of and in collaboration with the global societies of toxicologic pathology, the Society of Toxicologic Pathology initiated a review of OECD guidance no. 16. The objectives of this review are to provide a unified interpretation of the guidance, to recommend compliant processes for organizations to implement, and to avoid inconsistent process adaptations across the industry. This review of the guidance document is the product of a global collaboration with other societies of toxicologic pathology and provides a section-by-section international consensus view and interpretation of the OECD guidance on peer review.